Protection against peroxynitrite dependent tyrosine nitration and alpha 1-antiproteinase inactivation by some anti-inflammatory drugs and by the antibiotic tetracycline. Issue 6 (June 1996) - Whiteman, M; Kaur, H; Halliwell, B
Abstract : OBJECTIVE: To examine in vitro the ability of several drugs to protect against deleterious effects of peroxynitrite, a cytotoxic agent formed by reaction of nitric oxide with superoxide radical, that may be generated in the rheumatoid joint and could cause joint damage. METHODS: The ability of several drugs to protect against such possible toxic actions of peroxynitrite as inactivation of alpha 1-antiproteinase and nitration of tyrosine was evaluated. RESULTS: Most non-steroidal anti-inflammatory drugs were moderately (indomethacin, diclofenac, naproxen, tolmetin) or only weakly (sulindac, ibuprofen, aurothioglucose, flurbiprofen, sulphasalazine, salicylate, penicillamine disulphide) effective in preventing tyrosine nitration and alpha 1-antiproteinase inactivation by peroxynitrite, but 5-aminosalicylate and penicillamine were much more effective, as was the antibiotic tetracycline (but not ampicillin). Phenylbutazone and flufenamic acid protected effectively against tyrosine nitration, but could not be tested in the alpha 1-antiproteinase system. The analgesic paracetamol was highly protective in both assay systems. CONCLUSION: Many drugs used in the treatment of rheumatoid arthritis are unlikely to act by scavenging peroxynitrite. The feasibility of peroxynitrite scavenging as a mechanism of penicillamine, 5-aminosalicylate, and paracetamol action in vivo is discussed.